2005
DOI: 10.3354/meps286293
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium on diatom-copepod interactions

Abstract: From 3 to 6 November 2002, a colloquium was convened at the Benthos Laboratory of the Stazione Zoologica Anton Dohrn on Ischia, Italy, with the goal of evaluating the present status of the effects of diatoms on their main consumers, planktonic copepods, and to develop future research strategies to enhance our understanding of such interactions. These included (1) toxic effects of diatom metabolites on copepods, particularly reproduction, and (2) nutritional effects of diatoms on juvenile to adult copepods. Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 108 publications
2
41
0
Order By: Relevance
“…(2) The isolation and identiWcation of an unsaturated aldehyde from P. pouchetii (Hansen et al 2004) may indicate a line of defence that was recently revealed for diatoms (PaVenhöfer et al 2005, and references therein). Membrane lipids are converted into mildly toxic polyunsaturated fatty acids (PUFAs) by a grazing-activated enzymatic conversion.…”
Section: Introductionmentioning
confidence: 96%
“…(2) The isolation and identiWcation of an unsaturated aldehyde from P. pouchetii (Hansen et al 2004) may indicate a line of defence that was recently revealed for diatoms (PaVenhöfer et al 2005, and references therein). Membrane lipids are converted into mildly toxic polyunsaturated fatty acids (PUFAs) by a grazing-activated enzymatic conversion.…”
Section: Introductionmentioning
confidence: 96%
“…Accordingly, these studies are limited by problems arising from the extraction and identification of chemicals, as well as from the lack of realistic bioassays (Paffenhofer et al 2005;Van Holthoon et al 2003;Von Elert and Pohnert 2000). Matrix complexity, high dilution, and limited stability represent major challenges that have to be overcome during the identification of infochemicals from plankton.…”
Section: Introductionmentioning
confidence: 99%
“…T. weissflogii was second best, leading also to high naupliar survival rates and fast development, but to slower copepodite development. The successful use of T. weissflogii as a food organism is in contrast with the experimentally based view that diatoms in general are bad diet for raising copepods (Ianora et al 1995(Ianora et al , 2003Miralto 1999;Paffenhöfer et al 2005), while it agrees to field studies supporting a positive nutritional role of diatoms (Irigoien et al 2002). It is now well illustrated that not all diatom species per se are toxic, but even taxa lacking toxic metabolites can be insufficient to support copepod recruitment and development in mono-diet (Jones and Flynn 2005).…”
Section: Discussionmentioning
confidence: 61%